ANALISIS FATWA MAJELIS ULAMA INDONESIA TENTANG HUKUM MENJATUHKAN TALAK TIGA SEKALIGUS - Nur Nahdhiyatuz Zahro; Agus Supriyanto; Musyaffa Amin Ash Shabah (MASLAHAH (Jurnal Hukum Islam dan Perbankan Syariah), 2022)
This study analyzes the fatwa of the Indonesian Ulema Council in imposing three divorces at once and the factors that influence the fatwa of the Indonesian Ulema Council so that it imposes three simultaneous divorces. This research is qualitative, with a descriptive analysis method supported by normative law or literature study. Data collection, namely the fatwa of the Indonesian Ulema Council Three Divorces at Once, and books, journals, articles, and so on. The study's results explained that the decision of the fatwa of the Indonesian Ulema Council stated that divorces that occurred with three divorces at the same time resulted in one divorce law. In this decision, the Indonesian Ulema Council considered the opinion of the majority of scholars and Law no. 1 Marriage and the Compilation of Islamic Law as stated in article 115 KHI "Divorce can only be carried out before the trial of the Religious Court after the Religious Court has tried and failed to reconcile"